Optical Nonlinear Properties of Gold Nanoparticles Synthesized by Laser Ablation in Polymer Solution. (22nd February 2017) - Tajdidzadeh, M.; Zakaria, A. B.; Talib, Z. Abidin; Gene, A. S.; Shirzadi, S.
Abstract : In the present study, gold nanoparticles were synthesized in various polymer solutions by means of employing laser ablation technique at the same ablation time. Specifically, gold nanoparticles were synthesized in polyethylene glycol and chitosan solutions, in order to compare the effects of the liquid media which served as stabilizers for particle size and volume fraction of nanoparticles. In addition, this experiment was repeated in distilled water for reference purposes. As the findings indicated, the particle size which was obtained in polyethylene glycol was about 7.49 nm, that is, smaller than those of chitosan solution and distilled water, respectively. In contrast, it was observed that the volume fraction of gold nanoparticles increased in polyethylene glycol in comparison with the other media which indicated an effect on the formation of NPs. On the other hand, Z -scan technique was employed to measure the nonlinear refractive index and nonlinear absorption coefficient of nanofluids containing gold nanoparticles. Consequently, the nonlinear properties of nanofluids pointed to a significant contribution with the number of nanoparticles observed in fluids and both optical nonlinear parameters were observed to increase by means of a prior increase in the volume fraction of Au-NPs in polyethylene glycol solution.